2012
DOI: 10.1180/minmag.2012.076.8.53
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of radionuclides to a cementitious backfill material under near-field conditions

Abstract: The sorption behaviour of I À , Cs + , Ni 2+ , Eu 3+ , Th 4+ and UO 2 2+ on NRVB (Nirex reference vault backfill) a possible vault backfill, at pH 12.8 was studied. Sorption isotherms generated were compared to results obtained in the presence of cellulose degradation products (CDP). Whereas Cs was not affected by the presence of the organic compounds, a notable reduction in the sorption of Th and Eu to cement was observed. The results also indicated limited removal of Ni from solution (with or without an orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Ettringite (Ca 6 Al 2 (OH) 12 (SO 4 ) 3 ·26H 2 O; PDF 00-041-1451), calcium monocarboaluminate hydrate (Ca 4 Al 2 (OH) 12 (CO 3 ) 3 ·5H 2 O; PDF 01-087-0493) and calcium hemicarboaluminate hydrate (Ca 4 Al 2 (OH) 12 [OH (CO 3 ) 0.5 ]·5.5H 2 O; PDF 00-041-0221) were also identified. These results are in agreement with those identified previously in NRVB cured at ambient temperature (Felipe-Sotelo et al, 2012). While the phase assemblage for each formulation was similar, subtle differences were observed in the peak intensities of several reflections; monocarboaluminate reflections were more intense in NRVB (Ind) than NRVB (Lab), while reflections of calcite were more intense in NRVB (Lab), which is also apparent in the XRD patterns corresponding to limestone flour and CaCO 3 (Fig.…”
Section: Chemical Analysis (Hydration)supporting
confidence: 91%
See 1 more Smart Citation
“…Ettringite (Ca 6 Al 2 (OH) 12 (SO 4 ) 3 ·26H 2 O; PDF 00-041-1451), calcium monocarboaluminate hydrate (Ca 4 Al 2 (OH) 12 (CO 3 ) 3 ·5H 2 O; PDF 01-087-0493) and calcium hemicarboaluminate hydrate (Ca 4 Al 2 (OH) 12 [OH (CO 3 ) 0.5 ]·5.5H 2 O; PDF 00-041-0221) were also identified. These results are in agreement with those identified previously in NRVB cured at ambient temperature (Felipe-Sotelo et al, 2012). While the phase assemblage for each formulation was similar, subtle differences were observed in the peak intensities of several reflections; monocarboaluminate reflections were more intense in NRVB (Ind) than NRVB (Lab), while reflections of calcite were more intense in NRVB (Lab), which is also apparent in the XRD patterns corresponding to limestone flour and CaCO 3 (Fig.…”
Section: Chemical Analysis (Hydration)supporting
confidence: 91%
“…At high temperatures (80°C), the formation of hydrogarnet-type phases was also predicted, according to thermodynamic modelling (database not specified) performed by the same authors (Holland and Tearle, 2003), although more recent advances in cement chemistry and phase assemblage prediction models indicate that this may be less likely due to the high quantity of carbonate present in this cement formulation. Experimental X-ray diffraction (XRD) performed on fresh (uncured) NRVB revealed that the main phase present was calcite, whereas for NRVB cured for 4 months and 3 years, the phase assemblage was dominated by portlandite (Felipe-Sotelo et al, 2012).…”
Section: Nrvb Hydrationmentioning
confidence: 99%
“…The discussion of radionuclide transport begins with an overview of radionuclide behaviour research for the UK geological disposal programme by Sarah Vines and Rebecca Beard of the NDA (Vines and Beard, 2012). There follow papers which describe: the effect of cellulose degradation products on thorium sorption onto hematite including studies of a model ternary system by Stephen Swanton (AMEC) and co-workers (Baston et al, 2012b); uranyl binding to humic acid under conditions relevant to cementitious geological disposal of radioactive wastes by Anthony Stockdale and Nick Bryan (The University of Manchester) (Stockdale and Bryan, 2012); the sorption of radionuclides to a cementitious backfill material under near-field c o n d i t i o n s b y M ó n i c a F e l i p e -S o t e l o (Loughborough University) and co-workers (Felipe-Sotelo et al, 2012); the sorption properties of aged cements by Graham Baston (AMEC) and co-workers (Baston et al, 2012c); the effect of competition from other metals on nickel complexation by a-isosaccharinic, gluconic and picolinic acids by Nicholas Evans (Loughborough University) and co-workers ; and the complexation of Tc(IV) with EDTA and picolinic acid at high pH by Nicholas Evans and Ricky Hallam (Loughborough University) (Evans and Hallam, 2012).…”
Section: Section 7: Radionuclide Transportmentioning
confidence: 99%
“…Most studies on thorium focus on colloid generation phenomena (Fanghänel and Neck, 2002) given its low solubility and tendency to hydrolyse (Walther et al, 2008;Priyadarshini et al, 2016). Less attention has been paid to thorium adsorption (Wierczinski et al, 1998;Tits et al, 2000Cowper et al, 2006;Felipe-Sotelo et al, 2012) or incorporation into cement phases. Rothe et al (2013) and Bube et al (2014) characterised U(VI) phases in doped ordinary Portland cement (OPC): X-ray Absorption Near-Edge Structure (µ-XANES) and Raman spectroscopy indicated that the uranium solids formed were similar to diuranates (CaU2O7/Na2U2O7•xH2O).…”
Section: Introductionmentioning
confidence: 99%
“…The experiments include solubility determinations in a variety of alkaline solutions together with batch sorption, throughdiffusion and advection tests over extended periods of time, from several months to four years. The work forms part of a wider programme that, to date, has investigated adsorption (Felipe-Sotelo et al, 2012) and the mobility under near field conditions of Cl -(van Es et al, 2015), I -, Cs + , (Felipe-Sotelo et al, 2014), Ni 2+ (Felipe-Sotelo et al, 2016a) and SeO3 2-(Felipe-Sotelo et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%